2007
DOI: 10.1111/j.1442-9071.2006.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Periocular squamous cell carcinoma

Abstract: Squamous cell carcinoma (SCC) is the second most common eyelid malignancy and its incidence is increasing. Because of its variable clinical presentation, SCC may be difficult for even the experienced clinician to diagnose. Hence, all suspicious lesions warrant biopsy. As SCC behaviour may range widely in aggression, management should be individualized based on tumour (e.g. size, location, grade, histological subtype, previous recurrence, perineural invasion) and patient factors (e.g. age, health). Treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 109 publications
0
47
2
Order By: Relevance
“…Abstracting the data from our study and the few ones reported in the literature, PNI might represent an additional poor prognostic factor in patients with surgically treated CX. In cutaneous squamous cell carcinoma the histologic diagnosis of PNI might be an indication for adjuvant therapy (Limawararut et al 2007). Beitler et al (1997), in their study of recurrent CX treated with exenteration procedure, suggested that radiation therapy might be beneWcial to patients representing PNI.…”
Section: Discussionmentioning
confidence: 99%
“…Abstracting the data from our study and the few ones reported in the literature, PNI might represent an additional poor prognostic factor in patients with surgically treated CX. In cutaneous squamous cell carcinoma the histologic diagnosis of PNI might be an indication for adjuvant therapy (Limawararut et al 2007). Beitler et al (1997), in their study of recurrent CX treated with exenteration procedure, suggested that radiation therapy might be beneWcial to patients representing PNI.…”
Section: Discussionmentioning
confidence: 99%
“…6 While SCC is a less common periocular malignancy, 20-30% of periocular SCC is multifocal at the time of diagnosis 1,7 with regional involvement in between 1 and 24.3% of cases. 7,8 Perineural invasion occurs in 3-14% of squamous cell carcinomas and is associated with a worse prognosis. 1,8 SGC is a rare, aggressive cancer that not only spreads locally but also demonstrates significant metastatic potential with lymph node involvement present in 30% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Perineural invasion occurs in 3-14% of squamous cell carcinomas and is associated with a worse prognosis. 1,8 SGC is a rare, aggressive cancer that not only spreads locally but also demonstrates significant metastatic potential with lymph node involvement present in 30% of cases. 9,10 Reported overall mortality from SGC ranges from 18 to 30% and tumors that involve the upper and lower eyelids, are greater than 10mm in diameter, demonstrate pagetoid spread, or invade the orbit have a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed the inaccuracy of preoperative clinical diagnosis, by even experienced observers. [7][8][9][10][11][12] Fifteen of 51 lesions in our series were thought to be basal cell carcinoma and only 32 lesions (62.7%) were correctly identified as squamoproliferative lesions preoperatively. 7 Another study stated that the clinical diagnosis of SCC of the skin was confirmed in 51% of cases.…”
Section: ' Clinical Behaviourmentioning
confidence: 87%